The Struggle to Project a Positive Image of Dictatorial Argentina: The Military Government’s Efforts and Confrontations on the International Stage - Feld, Claudia; Catoggio, María Soledad (Hispania Nova, 2026)
This article reconstructs the ‘external front’ of Argentina’s last military dictatorship by analysing the state structures created to project a positive image abroad amid divisions within the military leadership. On the one hand, we show that this image had multiple facets and structures. On the other hand, we show that the issue of the disappeared detainees took some time to affect the country’s external image. Finally, we analyse two cases of great international impact - that of Elizabeth Käsemann and that of Alice Domon and Léonie Duquet - in order to understand how the different factions of the dictatorship implemented changing strategies to clean up the image discredited by the allegations and to avoid a rupture in bilateral relations.